Antimony telluride nanoplates for thermoelectric applications - Koh, Clarissa Wei Shan. (2009)
This project focuses on a novel solvothermal synthesis method of Antimony Telluride nanoplates in the pure and doped forms for thermoelectric applications. As compared with its bulk counterpart, Sb2Te3 has numerous added advantages, mainly attributed to its quantum confinement effect.